The Pasta Queen : a just gorgeous cookbook : 100+ recipes and stories - Munno, Nadia Caterina; Parla, Katie (Gallery Books, an imprint of Simon & Schuster, Inc., 2022)
"TikTok star and beloved home cook Nadia Caterina Munno, a.k.a. The Pasta Queen, presents a cookbook of never-before-shared recipes featuring the signature pasta tips and tricks that are 100% authentic to Italian traditions-and just as gorgeous as you are"--